DESIGNING A DATA WAREHOUSE FOR AIRLINE TICKET SALES AT PT ABC - Qadriah, Sekar Aurannisa Ramdhani; Beng, Jap Tji; Arisandi, Desi; Nagm, Fouad; Salsabila, Tasya Mulia; Zahro, Tiara; Dinatha, Vienchenzia Oeyta Dwitama (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2025)
The high demand for airline ticket purchases in Indonesia and ticket sales being one of the important assets for companies in the aviation industry. PT ABC requires a system that can effectively manage this data to support business analysis and strategic decision-making. This research aims to design a data warehouse that can integrate airline ticket sales data, enabling more efficient data storage, processing, and analysis. The approach used in the design of this data warehouse is the star schema, which consists of one main fact table and several dimension tables. The fact table contains ticket sales transaction data, while the dimension tables include information about time, flight routes, airlines, and customers. This research provides a primary contribution in the form of a data warehouse design that integrates airline ticket sales data, enabling faster and more accurate analysis. The resulting business impact includes increased operational efficiency, more accurate data-driven decision-making, and the ability to monitor sales trends in real-time through interactive dashboards. With this data warehouse, PT ABC can reduce data analysis time and improve the accuracy of sales trend predictions. Keywords: Data warehouse, Star Schema, PT ABC plane ticket sales, Business Intelligence.